Effectiveness of Vancomycin-Impregnated Bone Graft Substitutes for the Treatment of Chronic Osteomyelitis in Long Bones: Comparative Analysis - Alexander P. Antipov; Svetlana A. Bozhkova; Ekaterina M. Gordina; Alexander V. Afanasyev; Magomed S. Gadzhimagomedov (Travmatologiâ i Ortopediâ Rossii)
Background. Replacement of bone defects in the surgical treatment of chronic osteomyelitis is a key step to prevent recurrence of infection and potential fractures at the site of rehabilitation. Bone cement, biodegradable synthetic materials, as well as autologous, allogeneic, and xenogeneic bone tissue have become widespread in surgical practice. Giving these materials antibacterial properties will expand their use in the treatment of bone and joint infections, shorten the treatment time, and improve the patients’ quality of life.